(3NjQ GdHTQ HNjQ GdHTQs - (3CHh gGTe eMeO Hf CHj eMeO GHf XaQs ((3eOjfI efadhW s)
(3ChdgG (B:s
(3GdMeO ddg ehai ChdjGFg GdQaYI hGdJecjf heHdi CYOGFg CeG HYO agPG cJGH UfaJ Hg edM GdHTGQGJ GdebOeGJ Hjf jOi SjOfG GdfHi eMeO Udi Gddg Ydjg hSde CQHYI CUfGa aGdUfa GdChd eG LGA ef Pdc ai cJH Gddg GdSGdaI s
(3BNQgG (B:s
(3hbhdg cGdadL gh GdHYjQ Ph GdSfGejf hHYO abO CfgjJ cJGHi gPG Edi MOg Je cJGH NjQ GdHTQ HNjQ GdeHTQ Udi Gddg Ydjg hSde HMeO Gddg hYhfg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3HgGeT GdfSNI HYV GdJbjjOGJs
(3jdjg hQbGJ ajgG ahGFO WHjIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
Keywords: (3Gdabg GdESdGejs